Computerized assessment of placental calcification post‐ultrasound: a novel software tool. (1st April 2013) - Moran, M.; Higgins, M.; Zombori, G.; Ryan, J.; McAuliffe, F. M.
ABSTRACT: Objectives: Placental calcification is associated with an increased risk of perinatal morbidity and mortality. The subjectivity of current ultrasound methods of assessment of placental calcification indicates that a more objective method is required. The aim of this study was to correlate the percentage of calcification defined by the clinician using a new software tool for calculating the extent of placental calcification with traditional ultrasound methods and with pregnancy outcome. Methods: Ninety placental images were individually assessed. An upper threshold was defined, based on high intensity, to quantify calcification within the placenta. Output metrics were then produced including the overall percentage of calcification with respect to the total number of pixels within the region of interest. The results were correlated with traditional ultrasound methods of assessment of placental calcification and with pregnancy outcome. Results: The results demonstrate a significant correlation between placental calcification, as defined using the software, and traditional methods of Grannum grading of placental calcification. Whilst correlation with perinatal outcome and cord pH was not significant as a result of small numbers, patients with placental calcification assessed using the computerized software at the upper quartile had higher rates of poor perinatal outcome when compared with those at the lower quartile (8/22 (36%) vs 3/23 (13%); P  = 0.069). Conclusion: These results suggest that this computerized software tool has the potential to become an alternative method of assessing placental calcification. Copyright © 2012 ISUOG. Published by John Wiley & Sons, Ltd.